Survey of Children’s Interest in Traditional Games in Tulehu Village Central Maluku District - Siti Sabilla Ode; Bahmid Hasbullah; Siti Divinubun (Peneliti.net, 2023)
The purpose of this research is to find out how much the level of interest of school-age children in traditional games in Tulehu Village. The method in this research is descriptive quantitative research using a questionnaire to collect data. The sample used was 35 children consisting of 18 sons and 17 daughters. The instrument used is a questionnaire or interest questionnaire with several indicators, namely indicators of feeling happy, indicators of interest, indicators of attention and indicators of involvement. The results of the study regarding children’s interest in traditional games in Tulehu Village, Central Maluku Regency, were in the very low kirtera category of 6% or as many as 2 children, who were in the low category of 20% or as many as 7 children, who were in the medium category of 46% or as many as 16 children, who are in the high category of 20% or as many as 7 children and who are in the very high category of 9% or as many as 3 children. In conclusion, children’s interest in traditional games in Tulehu Village, Central Maluku Regency, is in the medium category or criteria.